Analisis Bibliometrik Perkembangan Teknologi Beton Serat (Fiber Reinforced Concrete) dengan Campuran Serat Alam - De Side, Gagassage Nanaluih; Khalil, Fakhrul Irfan; Zulfikar, Wahyudi; Putra, Guyup Mahardhian Dwi (LPPM Universitas Mataram, 2025)
The addition of natural fibers in concrete is of great interest in the field of construction materials. Compared to man-made fibers, natural fibers are cheaper and locally available. In addition, the use of natural fibers is certainly more eco-friendly than the use of synthetic fibers but can produce the same strength in its application as an additive. This study aims to determine the development trend of concrete technology with natural fiber admixtures, including the various types of natural fiber waste used, so that it can be a consideration and reference in the use of natural waste in the mix design of natural fiber concrete (Fiber Reinforced Concrete). This study uses bibliometric analysis and literature review methods using Publish or Perish/Harzing software and VOSviewer v.1.6.20. This study was conducted by bibliometric analysis method of concrete technology development that utilizes waste mixture as fiber in Google Scholar indexed publications from 2014 to 2023. Furthermore, the co-cite, coupler, and cluster analysis methods will be used to analyze the collaboration network, and VOSviewer v.1.6.20 is used to visualize this network with three visualization analyses; Network Visualization, Overlay Visualization, and Density Visualization. Of the total publications indexed by Google scholar, namely 989 documents, 958 documents have year information and 31 documents do not have information on the year of publication. The highest publication growth development with this topic occurred in 2021, which reached 284 publications (28.7%), while the lowest publication development was in 2024, totaling 10 documents (1%).